2018
DOI: 10.3389/fphys.2018.00701
|View full text |Cite
|
Sign up to set email alerts
|

Dental Findings in Patients With Non-surgical Hypoparathyroidism and Pseudohypoparathyroidism: A Systematic Review

Abstract: Background: Dental aberrations have been mentioned in relation to non-surgical hypoparathyroidism (Ns-HypoPT) and pseudohypoparathyroidism (PHP). However, a systematic review of dental characteristics have not been performed. The present systematic review describes the dental findings in patients with Ns-HypoPT and PHP.Methods: Studies on Ns-HypoPT and PHP reporting dental features were eligible. A systematic literature search was conducted using four bibliographic databases (Web of Science, Scopus, Pubmed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…In the present study, we found a higher frequency of pulp calcification, blunting of root apex, and shortening of root than previously reported [3]. However, only one of the previous studies included more than six patients [4].…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…In the present study, we found a higher frequency of pulp calcification, blunting of root apex, and shortening of root than previously reported [3]. However, only one of the previous studies included more than six patients [4].…”
Section: Discussionsupporting
confidence: 51%
“…The majority of former dental studies on patients with PHP are case reports or minor case series. In a recently published systematic review on dental anomalies in PHP [3], enamel hypoplasia occurred in 73% of the reported cases. In contrast, we found only eight (29%) patients with enamel hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental aberrations have been described in non-surgical hypoparathyroidism with symptoms including shortened roots, hypoplastic enamel and hypoplastic or absent teeth [67e69]. However, in the future, further studies should be conducted for better characterizing this complication [69].…”
Section: Dental Manifestationsmentioning
confidence: 99%